2022
DOI: 10.1155/2022/3839670
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Neutrophil-Lymphocyte Ratio and Platelet-Lymphocyte Ratio on Predicting Responsiveness to Neoadjuvant Chemoradiotherapy in Locally Advanced Rectal Cancer Patients

Abstract: Objective. Neutrophil-lymphocyte ratio (NLR) and Platelet-lymphocyte ratio (PLR) have been proposed as prognostic biomarkers in multiple cancers. However, the implications of NLR and PLR in the responsiveness to neoadjuvant chemoradiotherapy (nCRT) remain to be clarified in locally advanced rectal cancer (LARC) patients. This retrospective study investigated the prognostic value of NLR and PLR in nCRT responsiveness of LARC patients. Methods. A total number of 86 patients diagnosed with LARC and treated with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
8
2
Order By: Relevance
“…In the first day the difference among the two groups were more pronounced that second day; however, both associations were not significant ( p = 0.099 & p = 0.824). This finding in our study contradicts some of the other studies to date 7,9,10,17,24 . Furthermore, we did not discover any relationship between the sex of the patients and the presence of neurological symptoms.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the first day the difference among the two groups were more pronounced that second day; however, both associations were not significant ( p = 0.099 & p = 0.824). This finding in our study contradicts some of the other studies to date 7,9,10,17,24 . Furthermore, we did not discover any relationship between the sex of the patients and the presence of neurological symptoms.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding in our study contradicts some of the other studies to date. 7 , 9 , 10 , 17 , 24 Furthermore, we did not discover any relationship between the sex of the patients and the presence of neurological symptoms. Notably, we observed that younger children were more susceptible to present with neurological complications.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The probability of benefit from an ICI is significantly higher in the NLR low/TMB high group compared to the NLR high/TMB low group. Moreover, Liu et al [54] reported that the reduction in the NLR and PLR could predict the clinic remission rate and pathological responsiveness rate, respectively, in patients with rectal cancer. These findings suggest that these peripheral inflammatory indicators may be suitable candidates for a cost-effective and widely accessible biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…NLR indicates a patient's inflammatory state (neutrophil count) and adaptive immunity(lymphocyte count), which is determined from the number of neutrophils to lymphocytes measured in the peripheral blood. NLR is a straightforward and reliable biomarker for patient survival and surgical prognosis in a variety of disorders, including serious cardiac disease and numerous cancers [20][21][22].…”
Section: Introductionmentioning
confidence: 99%